STRATEGI PENGEMBANGAN EKONOMI ISLAM DI LEMBAGA KEUANGAN SYARI`AH "DINAR GROUP" - Zeni Lutfiyah (Journal of Law, Society, and Islamic Civilization, 2014)
Economic system of Sharia is considered to have a special market segment and promising, namely Muslims who constitute the majority of the Indonesian population. This system  will be one of the efforts to realize the ideals of civil society, although still always appear conceptual debate about technical implementation, marketing of products, as well as in terms of reaching the position in economic policy at the state level.This study intends to expose about ways that do the practitioners of Islamic economics in the Group Dinar preach Islamic economic system and its institutions as well as efforts to build resilience in the face of challenges and constraints that accompany it. especially with regard to the pattern of relationship coaching is done by the management group of the branches, and the strategies used in the face of competition in the same sector including product adaptation services to the needs of customers in the environment.